Cilnidipine Nanocrystals, Formulation and evaluation for Optimization of solubility and Dissolution Rate - Suray A. Al Hazzaa; Nawal A. Rajab (College of Pharmacy University of Baghdad, 2023)
Cilnidipine CLD fourth generation Ca+2 channel blockers, since cilnidipine has a very low solubility (BCS Class-II drug Low solubility High permeability) and extremely low medication compliance, it has been used to treat hypertension and hypertensive-associated vascular disorders.so cilnidipine can be formulated as nanocrystals NCs  using solvent anti-solvent technology which can improve the solubility and bioavailability .Two different stabilizers(poloxamer 188 and Tween20) were utilized to prepare  nine formula  with different ratio 1:0.25,1:0.5 and 1:1. Study and evaluation the formulation factors which may effect on particle size and Polydispersity index PDI. The prepared CLD NCs were evaluated for particle size and dissolution study ,F4 was the smallest size 152 nm ,PDI  (0.161 )and the saturated solubility was increased about ten folds, this formula was subjected for freeze drying by adding  3 % mannitol as cryoprotectant .A complete dissolusion was established in about 20 minutes  which confer the DSC and PXRD results in conversion from crystalline into amorphous state .It can conclude that solvent  anti-solvent technique was a useful in preparation of nanocrystals suspension .